(untitled) (Bangladesh Armed Forces Medical Journal, 2024)
Background: Autism Spectrum Disorder (ASD) is a neurodevelopment disorder and an emerging public health issue globally which is associated with huge burden to the family, community and the nation. Study was conducted to find out the coping strategies for financial burden of the family with ASD children. Methods: A cross-sectional study on 154 children with ASD was carried out from July 2015 to June 2016 where data were collected from two special schools and two specialized hospitals of Dhaka city. Data were collected by face-to-face interview with semi-structured questionnaire following systematic random sampling technique. Informed written consent was taken from the parents. Results: Majority (73.4%) of the children were male and average monthly family income and total treatment cost was Tk. 41785.7 and Tk. 23076.62 respectively. However, coping strategies were adopted by the family “changing lifestyle” (96.8%), “accepting the reality” (100%), “minimizing family investment” (90.3%). Again, 52.5% families minimized family investment as coping strategies, 52.2% families had financial constraint as consequences of financial burden, which were significantly higher in comparison with others (p<0.05). Conclusion: ASD foist huge financial burden to the families of affected children. To compensate this financial burden, families adopted different coping strategies like changing lifestyle, taking social support, relying on religion, minimizing family investment, accepting reality etc. Appropriate early diagnostic facilities should be available to estimate the actual burden of the country. Bangladesh Armed Forces Med J Vol 56 No (2) December 2023, pp 38-44